A note on the MUSIC algorithm for impedance tomography. (20th December 2016) - Hanke, Martin
Abstract: We investigate the MUSIC algorithm for the reconstruction of small (infinitesimal) inclusions inside a planar homogeneous object from discrete impedance tomography data within the framework of the gap electrode model. We provide a justification of the method whenever the number of electrodes exceeds 2( J + 1) where J is the number of the inclusions to be found.